(untitled) - Morville, Peter (Beijing, 2006)
Introducing information architecture. Basic principles of information architecture. Process and methodology. Information architecture in practice. Information architecture in the organization. Case studies: MSWeb an enterprise intranet, an online community.
Keywords: Web sites,Information storage and retrieval systems; Design,Architecture